(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Weaving, as one of humanity’s most ancient crafts, is undergoing a profound transformation driven by digitalization and material science. The modern weaving industry faces significant challenges, including environmental sustainability, global competition, and the need for integration with advanced manufacturing paradigms. This paper employs a systematic literature review methodology to analyze the fundamental processes of weaving and evaluate its future prospects. The key findings indicate a clear trajectory from traditional manual looms to automated, intelligent systems. Emerging areas such as 3D weaving for composites, smart textiles with integrated electronics, and sustainable practices are identified as primary growth vectors. The integration of Industry 4.0 technologies, including the Internet of Things (IoT) and artificial intelligence (AI), is poised to enhance efficiency and enable new applications in aerospace, medicine, and wearable technology. However, challenges such as high capital investment, the skills gap, and recycling complexities of multi-material textiles remain significant hurdles. The study concludes that the future of weaving lies in its convergence with other high-tech fields, positioning it as a critical discipline for manufacturing advanced materials and smart fabric systems.